Pendampingan Untuk Meningkatkan Pengetahuan Dasar-Dasar Wudlu Dengan Menggunakan Metode Demonstrasi Dan Metode Reward Pada Anak- Anak Majlis Taklim Baitul Iman Di Dusun Jati - Ulil Fikriyah; asyhari (LP3M IAIFA Kediri, 2021)
In Islam, it is worship that provides the spiritual practice needed by every human being. This is also the purpose of human life, namely worshiping Allah Subhanahu Wa Ta'ala. Thaharah is the most important feature in Islam, which means clean or holy person by birth or mind. Prayer will also not be legally done except by washing first. While wudlu is also called holy, because wudlu can cleanse itself of hadas and feces attached to the human body. In this wudlu learning, researchers use two methods, namely, the demonstration method and the reward method. Both of these methods are very helpful in the learning process that researchers carry out. So that researchers become easier in conveying the basic material of wudlu, and children are also more receptive to the material that researchers convey. In this study, researchers used the PAR (Participatory Action Research) method. The PAR method itself is an approach whose process aims to learn in overcoming problems and meeting the practical needs of society, as well as the production of science, and the process of religious social change. Here researchers directly participate in accompanying children in learning the basics of wudlu' in hopes of developing the child's Islamic character and good and true wudlu practice ability which is still classified as lacking.